Spatial processing and visual backward masking - Herzog, Michael H. (University of Finance and Management in Warsaw, 2008)
Most theories of visual masking focus prima-rily on the temporal aspects of visual information processing, strongly neglecting spatial factors. In recent years, however, we have shown that this position is not tenable. Spatial aspects cannot be neglected in metacontrast, pattern and un-masking. Here, we review these results.